THE AMBIGUITIES OF LOG DATA: SMART PHONES IN EVERYDAY LIFE - Thorhauge, Anne Mette; Lomborg, Stine (AoIR Selected Papers of Internet Research, 2014)
In this paper we will discuss the analysis of smart phone log data as an expression of everyday life. Smart phones have been celebrated recently as a versatile tool for collecting data about everyday life activities, owing to the integration of the smart phone in these very activities. On the one hand, we use the smart phone for documenting extraordinary and ordinary events of our lives by way of the phone’s built-in camera and video functionalities. On the other hand, our activities are recorded in various types of data formats such as communication histories, gps data and timestamps. These data tell a more indirect story about the way we live, how we move about, who are the most important persons in our lives, and so on.